Sustainable enhancement of Henequen fiber-reinforced polymer composites with copper oxide nanoparticles: A step forward in clean engineering and technology - Thandavamoorthy Raja; Yuvarajan Devarajan; Geetika M. Patel; Jayanta Kumar Nath; Aravindan Munusamy Kalidhas; Shweta Sharma; Pavan Chaudhary (Cleaner Engineering and Technology)
This study presents the development of environmentally sustainable Henequen fiber-reinforced polymer composites enhanced with copper oxide nanoparticles for clean engineering applications. Five composite variants were fabricated via the hand lay-up method with varying copper oxide loadings to investigate their influence on mechanical, thermal, and antibacterial properties. The composite with 15 g of copper oxide exhibited superior performance, achieving a tensile strength of 76.19 MPa, flexural strength of 81.29 MPa, impact strength of 17.92 kJ/m2, and Shore D hardness of 67. Microscopic analysis confirmed improved fiber–matrix adhesion and reduced fiber pull-out, while thermogravimetric analysis indicated enhanced thermal stability with 20 % char yield at 500 °C. Elemental mapping verified nanoparticle integration, and antibacterial assays revealed significant inhibition against Pseudomonas aeruginosa and Staphylococcus aureus, supported by biofilm disruption and oxidative cytotoxicity. These findings demonstrate the potential of copper oxide-reinforced natural fiber composites as biodegradable, antimicrobial, and high-performance materials aligned with the principles of clean and sustainable engineering.